COMMUNITY EDUCATION IN COMMUNITY DEVELOPMENT - Asep Saepudin; Dinno Mulyono (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2019)
In the framework of developing community education, education service programs, especially those related to improving community welfare, need to get special studies, especially in supporting theories implemented. It also implies new approaches, techniques and concepts that must be key words in building people's lives. Community education understands that corrections to past approaches need to be adjusted in the midst of continuous changes in the community, so that new studies are needed that are more in line with the challenges and needs of the community and new knowledge